Enhancing wear and corrosion resistance of TiO2-Al2O3 hybrid coatings by the development of TiO2-Al2O3 bilayer film coatings - Eraslan, Fatma Sezgi; Gecu, Ridvan (ELSEVIER SCI LTD, 2024)
Sol-gel fabricated TiO2-Al2O3 bilayer coatings were deposited on 316L surfaces with several combinations of layers. Microstructural, corrosion, and wear features of the fabricated film coatings were examined compared to the TiO2-Al2O3 hybrid coating containing 65 % TiO2, which achieved the highest protection against corrosion and wear in the previous study. The electrochemical properties were determined through electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization tests, whereas dry sliding tests were performed using an Al2O3 ball under 1 N. Regardless of the production parameters, rutile and alpha-Al2O3 phases were produced in all manufactured coatings with similar thicknesses. The coatings consisting of TiO2 at the top layers showed better anti-corrosive performance due to a dense, low-porosity, and continuous morphology of TiO2 nanoparticles, while the coatings containing Al2O3 at their top layers were determined to exhibit higher wear resistance. All bilayer film coatings increased the anti-corrosion and anti-wear performance of the hybrid coating.
Keywords: Bilayer coating; Sol-gel; Wear; Corrosion; SURFACE-MORPHOLOGY; ALUMINA COATINGS; STEEL; ANATASE; AL2O3; DEPOSITION; TRIBOLOGY; ROUGHNESS; BEHAVIOR; CARBON; Materials Science